INSTANT CUSTOMARY INTERNATIONAL LAW AND THE HUMAN RIGHT TO PRIVACY: HOW CAN IT MITIGATE THE DANGERS OF SURVEILLANCE SOCIETIES? - Suni, Joanna (My University, 2020)
This thesis shall analyse, how instant custom of international law may act as a mitigator for the issues presented by the modern surveillance societies. A multidisciplinary, non-dogmatic approach has been chosen to analyse the issue and as a result the sources vary from international treaties and other international regulation to as soft law sources. New challenges have risen and everyday life has changed. Societies are more interdependent and traditional societal boundaries fade. The concept of data privacy shall be examined in an international human rights context and an introductory look into surveillance societies and the possible dangers they create is taken. The main focus is in discussing the relationship between on surveillance societies and instant custom, and how instant custom can mitigate the dangers of surveillance societies. Speedy adaptation and transformation is required from international law. The instant custom approach provides a modern solution for the international legal field. Instant custom has the possibility to effectively mitigate not only the known dangers of surveillance societies, but also those still left unidentified. Custom is not an antiquated form of international law, but the answer to functional, modern, global international law.
Keywords: International customary law, instant custom, instant custom of international law, ICIL, CIL, customary law, surveillance societies, international law, privacy, data protection, personal data, globalisation, agile law